Teacher Training Policies in Japan in the Context of Ethical Values - LEVENT, AHMET FARUK (IGIAD-TURKISH ENTREPRENEURSHIP & BUSINESS ETHICS ASSOC, 2018)
Teachers hold significant roles and responsibilities in providing ethics education and in teaching fundamental values to learners at schools. They also play a critical role in enabling learners to construct their own value systems in terms of performing modeling and guiding tasks. The purpose of this study is to investigate teacher training policies in Japan in the context of ethical values. In accordance with this purpose, the information obtained from the literature review has been collected under three headings that address: Confucian teaching in Japan, the importance of ethics education in teacher education programs, and the effects of Confucian teachings on teacher training. Ethical codes regarding Confucian teachings for teachers are emphasized in teacher-training policies. Based on the obtained data, Confucian teachings such as respect, responsibility, honesty, justice, loyalty and modesty have been indicated to be considerably valued in the Japanese teacher-training system.
Keywords: Teacher training; Ethical values; Japan; Ethics education; Confucianism; CORPORATE CODES; EDUCATION; BUSINESS; CONFUCIANISM; MANAGEMENT; IMPACT; CHINA